Can gallium-68 prostate-specific membrane antigen ligand be a potential radiotracer for renal cortical positron emission tomography imaging? - Ismet Sarikaya; Abdelhamid Elgazzar; Mahmoud Alfeeli; Ali Sarikaya (World Journal of Nuclear Medicine)
Gallium-68 prostate-specific membrane antigen (Ga-68 PSMA) ligand (HBED-CC) is a new promising positron emission tomography (PET) tracer for prostate cancer. Intense renal parenchymal uptake is a physiologic finding on Ga-68 PSMA ligand PET images. Evaluation of kidneys in low intensity demonstrates excellent distribution of this radiotracer in renal parenchyma with excellent image quality and resolution. In this article, we present the Ga-68 PSMA ligand PET renal images of four patients with prostate cancer. In two patients, there is normal distribution of radiotracer, and in other two, there are renal cysts causing parenchymal defects.